Enhancing mechanisms of arc-erosion resistance for copper tungsten electrical contact using reduced graphene oxides in situ modified by copper nanoparticles. (November 2022) - Dong, LongLong; Li, Liang; Li, Xiang; Zhang, Wei; Fu, YongQing; Elmarakbi, Ahmed; Zhang, YuSheng
Abstract: To solve critical issues of premature failure for copper tungsten (CuW) based electrical contacts during arc erosion at the moment of arc breakdown, we proposed a new strategy of using metal doped reduced graphene oxides (rGOs) and in-situ formed tungsten carbides to inhibit movements of cathode spots during the arc ablation process. CuW composites were reinforced with Cu modified rGO nanopowders ( i.e. Cu@rGO) using combined processes of chemical co-reduction, ball milling and spark plasms sintering (SPS). Effects of Cu@rGO addition on microstructure, arc erosion resistance and arc ablation resistance of the CuW composites were systematically investigated. Results showed that tungsten carbides with irregular shapes were formed through in-situ reactions of rGO and tungsten during the SPS process. Arc erosion resistance of CuW composites was significantly improved owing to introduction of nanostructured Cu@rGO. Compared with those of CuW composites, the ablation areas of Cu@rGO/CuW ones were much smaller and the ablation craters were shallower, and the average strengths of dielectric vacuum breakdowns of the CuW composites with 3 wt% Cu@rGO were increased by 28.9%. The arc breakdown mechanisms of Cu@rGO/CuW composites were identified as: (1) The nanostructured Cu@rGO increases the viscosity of molten metal Cu, thus inhibiting its fast flow and splashing; (2) Lower work functions of carbon ( i.e. rGO) and tungsten carbide restrain the electron emissions during arc breakdown; and (3) The tungsten carbides with their good stability and high melting point shorten the solidification time of molten copper liquid and extend the service life time of the Cu@rGO/CuW composites. Highlights: Introduced nanostructured Cu@rGO into CuW improve effectively dispersion effect. Cu@rGO/CuW composites with smaller ablation area and shallower ablation craters. Average arc breakdown strength of 3wt%Cu@rGO/CuW composites increased by 28.9%. Arc breakdown mechanism were attributed to increasing of the viscosity of molten Cu, lower work functions of second phases. Provides a new thought of enhanced arc erosion resistance of CuW with graphene decorated with metal nanoparticles.